A new case of radiation-induced breast angiosarcoma. (2019) - Verdura, Vincenzo; Di Pace, Bruno; Concilio, Marina; Guastafierro, Antonio; Fiorillo, Gabriella; Alfano, Luigi; Nicoletti, Giovanni Francesco; Savastano, Clementina; Cascone, Anna Maria; Rubino, Corrado
Highlights: A biopsy of any suspicious breast skin lesion after radiotherapy is recommended. Patients with clinical anomalies post-breast cancer surgery and RT need attention. The Angiosarcoma was cured due to surgery and high-dose neoadjuvant chemotherapy. A correct 6 month follow-up is needed: check-ups, chest X-rays and ultrasound. The survival of the patient suggests possible ways to manage this rare tumour type. Abstract: Introduction: Radiation-induced breast angiosarcoma is a severe but rare late complication in the breast-preserving management of breast cancer through surgery and radiotherapy. Often the initial diagnosis is complex given its relatively anodyne nature and the fact that it usually presents in the form of typically multifocal reddish-purple papular skin lesions. Presentation of the case: We describe the clinical and pathologic findings of a 79-year-old woman, who developed a radiation-induced breast angiosarcoma after around 8 years. She initially refused a mastectomy leading to an adaptation in the management of this cancer. Discussion: The average latency of secondary angiosarcoma of the breast following radiation therapy is around six years. Breast angiosarcoma is typically considered to affect the dermis, and is therefore cutaneous in origin. An incisional biopsy of the discoloured skin and underlying mass is necessary. The treatment is surgical resection. The role of chemotherapy has not been clearly defined. Most data originate from retrospective case series studies suggesting that angiosarcomas are relatively sensitive to taxanes and anthracyclines. Conclusion: The preferred treatment is always aggressive surgical removal and, as our atypical clinical case suggests, neoadjuvant chemotherapy in very high doses is also needed. A biopsy of any suspicious breast skin lesion after radiotherapy is recommended. Despite the treatment challenges, our case provides enlightening details on the management of such a rare cancer even when faced with unplanned events which do not always allow for a textbook approach.